2018
DOI: 10.1002/ajmg.a.40481
|View full text |Cite
|
Sign up to set email alerts
|

Gene‐targeted deletion in mice of the Ets1 transcription factor, a candidate gene in the Jacobsen syndrome kidney “critical region,” causes abnormal kidney development

Abstract: Ets‐1 is a member of the Ets family of transcription factors and has critical roles in multiple biological functions. Structural kidney defects occur at an increased frequency in Jacobsen syndrome (OMIM #147791), a rare chromosomal disorder caused by deletions in distal 11q, implicating at least one causal gene in distal 11q. In this study, we define an 8.1 Mb “critical region” for kidney defects in Jacobsen syndrome, which spans ~50 genes. We demonstrate that gene‐targeted deletion of Ets‐1 in mice results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…1 Combined studies in humans and genetically engineered mice implicate the loss of the ETS1 (E26 transformation specific 1) transcription factor as the cause of CHDs and several other congenital defects in JBS. [11][12][13] ETS1 is a member of the ETS family of transcription factors. This family of transcription factors has important roles in a wide range of biological functions, including the regulation of cellular growth and differentiation as well as in organ development, vascular development and angiogenesis, and in the regulation of vascular inflammation and remodeling.…”
mentioning
confidence: 99%
“…1 Combined studies in humans and genetically engineered mice implicate the loss of the ETS1 (E26 transformation specific 1) transcription factor as the cause of CHDs and several other congenital defects in JBS. [11][12][13] ETS1 is a member of the ETS family of transcription factors. This family of transcription factors has important roles in a wide range of biological functions, including the regulation of cellular growth and differentiation as well as in organ development, vascular development and angiogenesis, and in the regulation of vascular inflammation and remodeling.…”
mentioning
confidence: 99%
“…Using KO ETS1 mice, Ye et al (2018) identified an overrepresentation of structural kidney defects, including unilateral duplicated ureters, duplicated kidneys, and unilateral renal hypoplasia. However, KO mice do not show complete dominance.…”
Section: Discussionmentioning
confidence: 99%
“…Concrescence may occur during root formation or after the radicular phase of development is completed. From the stages of tooth development, different degrees union of cementum, dentine, and enamel are possible [ 2 ], and the cause of tooth development abnormalities is hyperactivity of odontogenic epithelium [ 9 ]; the failure of the process of degeneration of the residual dental lamina cells leads to further reaction and over-proliferating and eventually develops into supernumerary teeth [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches are available for the treatment of supernumerary concrescence. The treatment can be performed in two means: (a) surgical extraction or (b) maintenance of the asymptomatic tooth and periodic monitoring at least once a year [ 9 ]. In this case, the impacted teeth led to pericoronitis sometimes, and they might cause the absorption and destruction of the distal neck bone in 37#.…”
Section: Discussionmentioning
confidence: 99%